Public perceptions of cybersecurity: a South African context - Toit, Ryan du (Acta criminologica, 2018)
As of September 2017, the US Federal Bureau of Investigation has ranked South Africa as sixth and seventh on the cybercrime predator list. This means that there is an increasing number of cybercrimes being perpetrated within the country. Although research into cybercrime has increased over the last decade, it is still a topic that remains unexplored, particularly from a social science perspective. The objective of this study was to collect baseline information regarding people’s perceptions and experiences of cybercrime within the South African context. An online questionnaire was completed by 248 respondents and covered a range of cybercrime related questions. It was found that 45.08 percent of respondents indicated that they had been targeted as a victim for cybercrime within the last year, with the two most common forms being; receiving spam e-mail (e.g. inheritance) and unsolicited pornographic images. In terms of reporting cybercrime, 45.95 percent of respondents indicated that they are ‘very willing’ yet 66.1 percent indicated that they do not report cybercrime, attributing this to being uninformed regarding how to report cybercrime activity. A small portion of the participants still regarded it inadequate practice to control and prevent cybercrime activities. Nearly 40 percent (39.9%) of the respondents felt that the current South African legislation on cybercrime failed to control cybercriminals. Just over half (51.2%) of the respondents were not sure whether South African law was able to control cybercriminals. Only eight percent of respondents had a strong belief that South African law was able to control cybercriminals. The findings of this study are discussed within the South African context, with the recommendation of increasing the publics’ accessibility to, and knowledge of, cybercrime laws, policies and reporting procedures.